Collective dynamics of neuronal activities in various modular networks. Issue 5 (21st January 2021) - Park, Myung Uk; Bae, Yonghee; Lee, Kyo-Seok; Song, Jun Ho; Lee, Sun-Mi; Yoo, Kyung-Hwa
Abstract : Three type of modular networks are constructed using polydimethylsiloxane (PDMS) microstructures fabricated on a multi-electrode array (MEA) without transfer to investigate how neuronal activities are affected by modular network structure. Abstract : Modularity is a key feature of structural and functional brain networks. However, the association between the structure and function of modular brain networks has not been revealed. We constructed three types of modular cortical networks in vitro and investigated their neuronal activities. The modular networks comprising 4, 3, or 2 modules were constructed using polydimethylsiloxane (PDMS) microstructures fabricated directly on a multi-electrode array (MEA) without transfer. The 4-module network had the strongest modular connectivity, followed by the 3-module and 2-module networks. To investigate how neuronal activities were affected by the modular network structure, spontaneous neuronal activities were recorded on different days in vitro and analyzed based on spike amplitudes, network bursts, and the propagation properties of individual spikes. Different characteristics were observed depending on the network topology and modular connectivity. Moreover, when an electrode was stimulated by biphasic voltage pulses, bursts were elicited for the 4-module network, whereas spikes were elicited for the 3-module and 2-module networks. Direct fabrication of the PDMS microstructures on the MEA without transfer allows microscale construction of modular networks and high-density functional recording; therefore, the technique utilizing the PDMS microstructures can be applied to the systematic study of the dynamics of modular neuronal networks in vitro .